Desenvolvimento de um medidor de baixo custo para atendimento aos novos requisitos de medição amostral dos indicadores de conformidade de nível de tensão - Oliveira, Lincoln Társio Silva (2022)
The Brazilian Electricity Regulatory Agency – ANEEL, through the Normative Resolution No. 871, of February 11, 2020, approved the revisions of the PRODIST modules 6 and 8, bringing significant changes for the sample measurement process of the voltage level conformity indicators, which starts to be measured with the use of permanent measuring systems, using a rotation model for meters allocation through a lottery to be carried out by ANEEL. Among other changes, it was also established the obligation of registering the last 12 values obtained for the relative transgression duration indicators for precarious and critical voltage level, DRP and DRC, as well as the last 100 short and long duration interruptions. Given the described scenario, this work initially aims to consolidate the measurement protocols necessary to meet the changes arising from ANEEL No. 871 Resolution of February 11, 2020, from the calculus of the voltage magnitude in steady state to the interruptions record. Regarding the DRP and DRC indicators, a critical analysis is done on the need to update the process of voltage levels evaluation with regard to the efficiency of the indicators, which alone are unable to even identify the type of problem (over or undervoltage). In this context, it is presented an alternative methodology to the one in effect to evaluate the conformity of voltage levels, based on voltage percentiles that define operation limits for adequate, upper and lower voltage ranges. As for their implementation, the difficulties present in creating equipment that meet the new obligations are discussed, as shown during different tests. These tests expose a series of deficiencies in the equipment available in the market. To finish, this work represents the results obtained in the development of a low-cost voltage meter prototype, which objective was fully meeting the new obligations, showing the process of creating it since the modelling part in Simulink’s environment to composing the implemented hardware.